Smart Business Process Management: An Introduction - Dash, Sidhya B (International Journal of Psychosocial Rehabilitation, 2019)
Processes have become an important asset in organizations for daily life over the past decade because an organization’s sufficient Business Process Management (BPM) (e.g. software development firms) will help achieve organizational goals. In particular, it is important to control these processes effectively, which are essential for organizational success, in order to continually improve, while increasing productivity and profitability within the enterprise (e.g. software processes in software companies). This process is related to the lifecycle of the project and currently there are many tools (Business Process Management Suites, BPMS) for managing this lifecycle. Although, not all BPMSs provide complete support for this lifecycle, this makes choosing the right BPMS more difficult (depending on the organization’s needs). This paper presents principles of smart business process management and serves as an editorial for the particular issue in question. Author presents a structure that defines three types of business process management: multi-process management, process model management, and management of process instances.